1986
DOI: 10.1152/ajpheart.1986.250.3.h372
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial actions of superoxide dismutase and catalase in stunned myocardium of dogs

Abstract: Recent evidence suggests that oxygen free radicals may partially mediate irreversible ischemia-reperfusion injury in the myocardium. In the present study, the effect of a combination of two oxygen free radical scavengers, superoxide dismutase plus catalase (SOD + CAT), on the recovery of subendocardial segment function following 15 min of coronary artery occlusion followed by 3 h of reperfusion ("stunned" myocardium) was compared with a control group in barbital-anesthetized dogs. Myocardial segment shortening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
2
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 0 publications
4
68
2
1
Order By: Relevance
“…The majority of the studies demonstrating beneficial effects have been conducted in open chest anesthetized animals studied for a relatively short period of time (i.e., 2 days or less). [9][10][11][29][30][31][32][33] Perhaps, in the present study, if treatment had been continued for a longer period or if animals had been studied for a shorter period of time, the beneficial effects of SOD would have been more evident. However, if this therapy is to be useful in patients, it must exert a beneficial effect for a far greater period of time than 1 week to be clinically efficacious.…”
Section: Arrhythmiasmentioning
confidence: 74%
“…The majority of the studies demonstrating beneficial effects have been conducted in open chest anesthetized animals studied for a relatively short period of time (i.e., 2 days or less). [9][10][11][29][30][31][32][33] Perhaps, in the present study, if treatment had been continued for a longer period or if animals had been studied for a shorter period of time, the beneficial effects of SOD would have been more evident. However, if this therapy is to be useful in patients, it must exert a beneficial effect for a far greater period of time than 1 week to be clinically efficacious.…”
Section: Arrhythmiasmentioning
confidence: 74%
“…Recent evidence suggests that postischaemic myocardial dysfunction (stunning) may represent a functional or nonlethal form of reperfusion injury (Braunwald & Kloner, 1982;Kloner et al, 1989) and oxygen free radicals may contribute to the pathogenesis of myocardial stunning (Gross et al, 1986;Bolli et al, 1987;1989;Forman et al, 1988;Faber et al, 1988). Bolli and his colleagues (1988) using electron paramagnetic resonance spectroscopy detected a burst of free radical formation within the coronary venous effluent in dogs subjected to 15min of coronary occlusion and reperfusion; other studies found that production of free radicals increased markedly in isolated hearts of rabbit or rat undergoing global ischaemia and reperfusion (Zweier et al, 1987;Garlick et al, 1987; Kramer et al, 1987) and pretreatment with the oxygen radical-scavenging agents superoxide dismutase and catalase reduced the degree of left ventricular dysfunction in canine models of stunned myocardium (Gross et al, 1986;Ambrosio et al, 1987;. Nevertheless, recent studies also indicate that other factors independent of free radicals are involved in the pathogenesis of myocardial stunning such as: calcium overload (Kusuoka et al, 1987; Lee et al, 1987;Steenbergen et al, 1990;Sun & Lin, 1990), heterogeneous impairment of myocardial perfusion (Stahl et al, 1986) and neutrophil accumulation in the postischaemic myocardium (Westlin & Mullane, 1989) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…3 After that, Bolli defined myocardial stunning as the mechanical dysfunction that persists after reperfusion despite the absence of irreversible damage. 4 Both the failure of calcium homeostasis 5,6 and the generation of oxygen-derived free radicals [7][8][9][10][11][12] have been scrutinized as potentially major causes of reperfusion injury after brief ischemia. However, there is little evidence of any correlation between the loss of calcium homeostasis and the burst of free radicals.…”
mentioning
confidence: 99%